THALAMOCORTICAL PROCESSING IN VISION - Mazade, Reece (Vis Neurosci, 2017)
Visual information reaches the cerebral cortex through a major thalamocortical pathway that connects the Lateral Geniculate Nucleus (LGN) of the thalamus with the primary visual area of the cortex (area V1). In humans, ~3.4 million afferents from the LGN are distributed within a V1 surface of ~2,400 mm(2), an afferent number that is reduced by half in the macaque and by more than two orders of magnitude in the mouse. Thalamocortical afferents are sorted in visual cortex based on the spatial position of their receptive fields to form a map of visual space. The visual resolution within this map is strongly correlated with total number of thalamic afferents that V1 receives and the area available to sort them. The ~20,000 afferents of the mouse are only sorted by spatial position because they have to cover a large visual field (~300 degrees) within just 4 mm(2) of V1 area. By contrast, the ~500,000 afferents of the cat are also sorted by eye input and light/dark polarity because they cover a smaller visual field (~200 degrees) within a much larger V1 area (~ 400 mm(2)), a sorting principle that is likely to apply also to macaques and humans. The increased precision of thalamic sorting allows building multiple copies of the V1 visual map for left/right eyes and light/dark polarities, which become interlaced to keep neurons representing the same visual point close together. In turn, this interlaced arrangement makes cortical neurons with different preferences for stimulus orientation to rotate around single cortical points forming a pinwheel pattern that allows more efficient processing of objects and visual textures.